Upaya Meningkatkan Motivasi dan Prestasi Belajar Mahasiswa dengan Pembelajaran Kooperatif Tipe Thinking Aloud Pairs Problem Solving Pada Mata Kuliah Aljabar Linear - Dwi Cahyani Nur Apriyani (Beta: Jurnal Tadris Matematika, 2015)
The purpose of this study was undertaken to: (1) enhance learning motivation of students in linear algebra lecture through cooperative learning Thinking Aloud Pairs Problem Solving, (2) improve the achievement of students in linear algebra lecture through cooperative learning Thinking Aloud Pairs Problem Solving. This research is a classroom action research conducted in two cycles. Each cycle includes four phases: planning action, action, observation / evaluation and reflection. The results obtained in each cycle of this study are as follows. The results obtained in the first cycle is only 14 students or 17.07% of students who scored at least 70 of learning achievement tests among all students. It means the condition is still under the success indicator of this research, which is 60%. The second result was the average score of students learning motivation questionnaire is 48 (scale 15-75),which is high category. Because the condition is still under the success indicator so it needs to be continued into the next cycle. Results in the second cycle showed an increase from the first cycle in terms of both achievement and motivation to learn. Results of the second cycle that are 56 or 68.29% of students who scored at least 70 of learning achievement tests among all students so that indicators of success has been achieved as well as the average score of student motivation questionnaire is 50, which means at the high category.